EVALUASI DAMPAK PERUBAHAN PENGGUNAAN LAHAN TERHADAP VOLUME LIMPASAN STUDI KASUS: DAS CILIWUNG HULU, JAWA BARAT (EVALUATION OF LANDUSE CHANGE IMPACT ON RUN-OFF VOLUME CASE STUDY : CILIWUNG HULU WATERSHED, WEST JAVA) - B. D. Dasanto; . Risyanto (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2006)
The upper Ciliwung watershed is one of the critical catchments areas in Java Island. A major element of this area is the modification of natural land-cover due to human activities. Land use change is driven by the interaction between physical and socio-economic factors. The objective of this paper is to develop a land use change model and to evaluate runoff volume based on land use prediction. The pseudo-R2 or 2 in this model is 51.7% and the calibration between predicted land use and the real is 65.5%. The analysis result of land use change for period 2005-2010 and 2015-2020 show a special change pattern. In the first period, the forest land will decrease by 85%, while resettlements land increase by 144%, so the Curve Number value will increase from 80 to 81. These indicate decreasing capability of the upper Ciliwung to retain rainfall. The impact of this condition will increase runoff volume from 660.000 m3 to be 905.000 m3. In the second period, the forest and resettlements land will increase by 612% and 28%, so the Curve Number will decrease from 80 to be 78. This will decrease runoff volume from 805.000 m3 to be 803.000 m3.